MRI‐based score to predict surgical difficulty in patients with rectal cancer. Issue 1 (31st October 2017) - Escal, L.; Nougaret, S.; Guiu, B.; Bertrand, M. M.; de Forges, H.; Tetreau, R.; Thézenas, S.; Rouanet, P.
Abstract : Background: Rectal cancer surgery is technically challenging and depends on many factors. This study evaluated the ability of clinical and anatomical factors to predict surgical difficulty in total mesorectal excision. Methods: Consecutive patients who underwent total mesorectal excision for locally advanced rectal cancer in a laparoscopic, robotic or open procedure after neoadjuvant treatment, between 2005 and 2014, were included in this retrospective study. Preoperative clinical and MRI data were studied to develop a surgical difficulty grade. Results: In total, 164 patients with a median age of 61 (range 26–86) years were considered to be at low risk (143, 87·2 per cent) or high risk (21, 12·8 per cent) of surgical difficulty. In multivariable analysis, BMI at least 30 kg/m 2 ( P  = 0·021), coloanal anastomosis ( versus colorectal) ( P  = 0·034), intertuberous distance less than 10·1 cm ( P  = 0·041) and mesorectal fat area exceeding 20·7 cm 2 ( P  = 0·051) were associated with greater surgical difficulty. A four‐item score (ranging from 0 to 4), with each item (BMI, type of surgery, intertuberous distance and mesorectal fat area) scored 0 (absence) or 1 (presence), is proposed. Patients can be considered at high risk of a difficult or challenging operation if they have a score of 3 or more. Conclusion: This simple morphometric score may assist surgical decision‐making and comparative study by defining operative difficulty before surgery. Abstract : Imaging criteria predict surgical difficulty